THE EFFECTIVENESS OF PROBING QUESTIONS STRATEGY IN THE DEVELOPMENT OF THINKING SKILLS IN THE ISLAMIC EDUCATION COURSES USING A SAMPLE OF INTERMEDIATE SCHOOL STUDENTS IN RIYADH - Adel Ayed AL Magthwi (European Scientific Journal, ESJ, 2015)
Importance of the study: Current study may be useful for Islamic education teachers to improve their performance in light of using of probing questions strategy for Teaching Islamic education courses and the development of thinking among the students of the middle stage, and not only on the using of strategies such as the lecture for the development of only memorization and recall skills. The present study aimed to: 1. Enhanced knowledge of the reality of teaching practices and exercise enhanced probing questions strategy by teachers of middle stage. 2. Enhanced knowledge of the effectiveness of probing questions strategy in the development of thinking in Islamic Education courses at a sample of the middle stage students in Riyadh. The problem of the study is concentrated on the following question: What is the effectiveness of probing questions strategy in the development of thinking skills in the courses of Islamic Education at a sample of the preparatory grade students in Riyadh? The researcher was able to formulate the following null hypotheses to answer her main question: 1. There is no difference statistically significant at the level of significance (α ≤ 0.05) between the average post-test scores for the experimental group and control group in the skills of thinking. To ensure the correct of hypotheses of the study The researcher was able to use the experimental method on a sample deliberate of students from third grade of preparatory school number of students: (59) student applied them to the experience of the study and the researcher prepared the test for measuring thinking skills, as used retail mid-term to ensure the validity of this test and its reliability by the application of tribal for them at the two study groups, as was applied to the two groups after the completion of the experiment, while the test was used (T-Test) as a way to statistically processing the results and see significant differences between the two groups. The study resulted in: 1. There are significant differences between the average degrees of post-test for two groups in the level of skills of thinking in favor of the group experimental. In light of the results of the study, the researcher recommended a number of recommendations including: 1. The education departments of the Ministry of Education conduct some training courses for teachers in various disciplines about the teaching strategies of using the probing questions strategy; and the development of thinking that is done on a regular basis to include all parameters. 2. Training the teachers of all subjects to develop the levels of thinking of students and to be done on a regular basis to include all teachers.